2017
DOI: 10.1039/c6cc09213f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the molecular determinants of fluorinase specificity

Abstract: Molecular determinants of FlA1 fluorinase specificity were probed using 5'-chloro-5'-deoxyadenosine (5'-ClDA) analogs as substrates and FlA1 active site mutants. Modifications at F213 or A279 residues are beneficial towards these modified substrates, including 5'-chloro-5'-deoxy-2-ethynyladenosine, ClDEA (>10-fold activity improvement), and conferred novel activity towards substrates not readily accepted by wild-type FlA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…Upon comparison of the halide ion binding site, an attempt was made to convert the chlorinase to a fluorinase by substituting the respective halide-binding residues. 57,66 Structural 67,68 and computational studies 69 of the fluorinase and chlorinase provided insights into the mechanism of halide selection. Crystal structures of the fluorinase in complex with chloride ion (since F − is indistinguishable from water) showed that the halide coordination is reliant on S158 and T80 in the fluorinase which are substituted with G131 and Y70 in the chlorinase, respectively (Fig.…”
Section: Fluorination Biocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon comparison of the halide ion binding site, an attempt was made to convert the chlorinase to a fluorinase by substituting the respective halide-binding residues. 57,66 Structural 67,68 and computational studies 69 of the fluorinase and chlorinase provided insights into the mechanism of halide selection. Crystal structures of the fluorinase in complex with chloride ion (since F − is indistinguishable from water) showed that the halide coordination is reliant on S158 and T80 in the fluorinase which are substituted with G131 and Y70 in the chlorinase, respectively (Fig.…”
Section: Fluorination Biocatalystsmentioning
confidence: 99%
“…In recent advances in biocatalytic fluorination, more complex analogs of the traditional 5′-FDA were prepared through late-stage fluorination of C2-substituted molecules, including those bearing click-chemistry handles. 66,70 One shortcoming of biocatalysis is that enzymes tend to exhibit reduced catalytic efficiency with unnatural substrates, which has been observed in the previously discussed halogenases, and fluorinases are no exception. Saturation mutagenesis was used to generate more active mutants, while reaction conditions such as temperature and leaving group options on the substrate were optimized.…”
Section: Fluorination Biocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] To explore this in more detail, we obtained two structures of wild-type SalL with SAM and chloride (6RYZ, 1.50 ), and with ClDAa lone (6RZ2, 1.77 ; Figure 2, Supporting Information, Table S1). [38][39][40] To explore this in more detail, we obtained two structures of wild-type SalL with SAM and chloride (6RYZ, 1.50 ), and with ClDAa lone (6RZ2, 1.77 ; Figure 2, Supporting Information, Table S1).…”
mentioning
confidence: 99%
“…An earlier structural study of SalL in complex with ClDA and methionine revealed as olvent-exposed channel into the active site. [38][39][40] To explore this in more detail, we obtained two structures of wild-type SalL with SAM and chloride (6RYZ, 1.50 ), and with ClDAa lone (6RZ2, 1.77 ; Figure 2, Supporting Information, Table S1). One significant difference in our structures compared to those obtained previously was arotation of the sidechain of Arg243, from the solvent-exposed exterior of the protein to the interior of the active site,enabling the formation of electrostatic interactions between Arg243 and the carboxylate of SAM (Figure 2a nd Supporting Information, Figure S1), and the side chain of Glu17 from the adjacent monomer.Noassociated changes in the solvent-exposed channel were observed.…”
mentioning
confidence: 99%